How India's mainstream media report on the farmers' protest. Issue 1 (9th January 2022) - Anand, Abhijit; Sharma, Parth
Abstract: The recently passed farm laws in the parliament created a huge uproar in India. The government touted them as a historic step that would allow farmers to sell their produce outside the Agricultural Price Marketing Committee/Mandis anywhere in India to wholesale agents, cold storage farms. It allows them to go for contract farming, and so forth. But many farmers groups and opposition parties consider it as a death warrant for them which would eventually expose farmers to vagaries of the market and thereby impoverish them in the long run. Various farmers groups have been protesting against the farm bills since then. India's mainstream media has notoriously sided with the government's narrative and has tried to delegitimize their movement against the farm acts. They have labeled them as separatists, Maoists, and Khalistani terrorists.